2007
DOI: 10.1063/1.2749866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser sources on the reverse-bias leakages of laser lift-off GaN-based light-emitting diodes

Abstract: The KrF pulsed excimer laser (248nm) and the frequency-tripled neodymium doped yttrium aluminum garnet laser (355nm) have been used to separate GaN thin films from sapphire substrates and transfer to bond other substrate. However, these processes would increase the dislocation density, resulting in an increase of the leakage current. In this study, the effects of these two laser sources on the reverse-bias leakages of InGaN-GaN light-emitting diodes were studied. (c) 2007 American Institute of Physics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 10 publications
1
46
0
Order By: Relevance
“…However, in the case of the LLO process, there is a problem to decompose the GaN into liquid gallium and gaseous nitrogen [3,4]. Moreover, there is local heating over the critical sublimation temperature of gallium, the LLO process inevitably causes a considerable degradation of GaN [5]. Recently, Ha et al [1] reported new method for fabricating vertical LED by using the chemical lift-off (CLO) process.…”
Section: Introductionmentioning
confidence: 98%
“…However, in the case of the LLO process, there is a problem to decompose the GaN into liquid gallium and gaseous nitrogen [3,4]. Moreover, there is local heating over the critical sublimation temperature of gallium, the LLO process inevitably causes a considerable degradation of GaN [5]. Recently, Ha et al [1] reported new method for fabricating vertical LED by using the chemical lift-off (CLO) process.…”
Section: Introductionmentioning
confidence: 98%
“…This fact manifests that the atomic movements needed for the observed dislocation generation and MQW intermixing are mainly due to the combined effects of REDR and the phonon generation as the generated electrons and holes move to their relevant band edges to recombine, while many people have argued that the generation and propagation of shock wave at/from the GaN/Al 2 O 3 interface would be the main origin of the increase of the dislocations in the bottom GaN layer after the LLO process. [5][6][7] This reasoning can also explain how the QW intermixing may be so apparent even with a rather small number of the KrF photons arriving at the MQWs (1.5 × 10 16 /cm 2 ). The difference between the KrF photon energy and the bandgap energy of GaN (In 0.3 Ga 0.7 N) is 1.6 (2.2) eV.…”
Section: Fig 5 (A)mentioning
confidence: 99%
“…5 The screw dislocations generated by the LLO process are believed to lead to an increase in the leakage current in the vertical LEDs. 6 Even though many studies have been reported on the damage effect of the LLO process on the GaN layers, 5-9 few works have been reported on the effects of the LLO process on the InGaN/GaN multiple quantum well (MQW) layers of the GaN-based LEDs. And most of the reported optical studies have been performed by using photoluminescence (PL) characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations